Optimizing Learning Experiences: A Study of Student Satisfaction with LMS in Higher Education - Ayubi, M. Nizar; Retnowardhani, Astari (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research delves into the examination of student satisfaction regarding the use of Learning Management Systems (LMS) through a comprehensive questionnaire distributed among 326 participants. The study adopts a modified DeLone and McLean is Model as its methodology to assess various dimensions of LMS satisfaction. Utilizing SmartPLS for hypothesis testing, the study rigorously analyzes the data collected. The findings indicate the acceptance of all proposed hypotheses, revealing significant correlations among the variables under scrutiny. A notable outcome is the identification of service quality as the most prominent influencer of student satisfaction within LMS environments. This underscores the critical imperative for higher education institutions to prioritize and address service quality concerns proactively. Practical solutions may encompass optimizing technical support structures, refining user interfaces for enhanced accessibility, ensuring system stability, and facilitating ongoing training and support initiatives. By addressing these pivotal areas, institutions can elevate the overall student learning experience and enhance the efficacy of LMS platforms in facilitating robust educational outcomes.